Effect of severe renal impairment on umeclidinium and umeclidinium/vilanterol pharmacokinetics and safety: a single-blind, nonrandomized study - Mehta, Rashmi; Hardes, Kelly; Brealey, Noushin; Tombs, Lee; Preece, Andrew; Kelleher, Dennis (International journal of chronic obstructive pulmonary disease, 2015)
BACKGROUND: Umeclidinium and vilanterol, long-acting bronchodilators for the treatment of chronic obstructive pulmonary disease, are primarily eliminated via the hepatic route; however, severe renal impairment may adversely affect some elimination pathways other than the kidney. OBJECTIVES: To evaluate the effect of severe renal impairment on the pharmacokinetics of umeclidinium and umeclidinium/vilanterol. METHODS: Nine patients with severe renal impairment (creatinine clearance <30 mL/min) and nine matched healthy volunteers received a single dose of umeclidinium 125 μg; and after a 7- to 14-day washout, a single dose of umeclidinium/vilanterol 125/25 μg. RESULTS: No clinically relevant increases in plasma umeclidinium or vilanterol systemic exposure (area under the curve or maximum observed plasma concentration) were observed following umeclidinium 125 μg or umeclidinium/vilanterol 125/25 μg administration. On average, the amount of umeclidinium excreted in 24 hours in urine (90% confidence interval) was 88% (81%-93%) and 89% (81%-93%) lower in patients with severe renal impairment compared with healthy volunteers following umeclidinium 125 μg and umeclidinium/vilanterol 125/25 μg administration, respectively. Treatments were well tolerated in both populations. CONCLUSION: Umeclidinium 125 μg or umeclidinium/vilanterol 125/25 μg administration to patients with severe renal impairment did not demonstrate clinically relevant increases in systemic exposure compared with healthy volunteers. No dose adjustment for umeclidinium and umeclidinium/vilanterol is warranted in patients with severe renal impairment.
Keywords: práškové inhalátory; benzylalkoholy; Humans; Quinuclidines; Administration, Inhalation; Kidney Diseases; lidé středního věku; fixní kombinace léků; nemoci ledvin; exposure; chronic obstructive pulmonary disease; Female; Aged; Area Under Curve; dospělí; Dry Powder Inhalers; long-acting muscarinic antagonist; chinuklidiny; Bronchodilator Agents; senioři; lidé; Benzyl Alcohols; antagonisté muskarinových receptorů; agonisté beta-2-adrenergních receptorů; Hungary; Muscarinic Antagonists; Maďarsko; Adrenergic beta-2 Receptor Agonists; Adult; ženské pohlaví; Single-Blind Method; stupeň závažnosti nemoci; Male; Middle Aged; long-acting beta2 agonist; Czech Republic; Renal Elimination; GSK573719; aplikace inhalační; Severity of Illness Index; plocha pod křivkou; Chlorobenzenes; jednoduchá slepá metoda; Česká republika; mužské pohlaví; Drug Combinations; chlorbenzeny; eliminace ledvinami; bronchodilatancia